12= 1*5^1+2*5^0
5+2
7
34=3*5^1+4*5^0
15+4
19
42=4*5^1+2*5^0
20+2
22
120=1*5^2+2*5^1+0*5^0
25+10+0
35
213=2*5^2+1*5^1+3*5^0
100+5+3
108
430=4*5^2+3*5^1+0*5^0
400+15+0
415
quinary
2. What are the last 2 digits of 1 + 2 + 3 + + 2005 2006
Let S be the sum. So you have
S = 1 + 2 + 3 + … + 2004 + 2005 + 2006
as well as
S = 2006 + 2005 + 2004 + … + 3 + 2 + 1
Then
2S = (1 + 2006) + (2 + 2005) + … + (2005 + 2) + (2006 + 1)
2S = 2007 + 2007 + … + 2007 + 2007
2S = 2006 × 2007
S = (2006 × 2007)/2
S = 2,013,021
which makes the last two digits 21.
Find the solution to the system of equation -x + y = 3 and x - 2y = 5.
Answer:
Step-by-step explanation:
[tex]\displaystyle\ \large \boldsymbol{} +\left \{ {{-x+y=3} \atop { \ \ x-2y=5}} \right. => \\\\\\x \!\!\!\!\diagup-x\!\!\!\!\diagup-2y+y=5+3\\\\-y=8\\\\ y=-8\ ; \ x=-11[/tex]
Please help out with this question..
Answer:
Step-by-step explanation:
C = 16 * 3 = 48
Match each equation with its solution.
Answer:
1. x = -2 , 3
2. x = - 1, 5
3. -1, 6/5
4. - 0/3, 1.3
Step-by-step explanation:
1.
[tex]ln(x+5)=ln(x-1)+ln(x+1)\\\\x+ 5 = (x-1)(x+1)\\\\x + 5 = x^2 - 1\\\\x^2 - x - 6 = 0 \\\\x^2 - 3 x + 2 x - 6 =0 \\\\x(x-3)+2(x-3)=0\\\\x = -2 and 3[/tex]
2.
[tex]e^{x^{2}}=e^{4x +5}\\\\x^2 - 4x - 5 = 0 \\\\x^2 - 5x + x - 5 = 0 \\\\x (x-5)+1 (x-5)=0\\\\x = -1 and 5[/tex]
3.
[tex]log_{4}(5x^2 +2)=log_{4}(x +8)\\\\5x^2 - x - 6 = 0 \\\\5 x^2 - 6 x + 5x- 6 = 0 \\\\5 x (x + 1)-6(x+1)=0\\\\x = -1 and \frac{6}{5}[/tex]
4.
[tex]log(x-1)+log 5x = 2\\\\5 x (x-1) =2 \\\\5x^2 - 5x -2 = 0 \\\\x = \frac{5\pm\sqrt{25+40}}{10}\\\\x = \frac{5\pm 8}{10}\\\\x = 1.3, - 0.3[/tex]
I need help on this question 5=7+x/5
Answer:
-10 = x
Step-by-step explanation:
5=7+x/5
Subtract 7 from each side
5-7=7-7+x/5
-2 = x/5
Multiply each side by 5
-2 *5 = x/5 *5
-10 = x
Do you remember how to solve a multistep linear equation with variables on both sides? Review with a Quick Check.
Solve:
5(a−1)−15=3(a+2)+4
Answer:
Step-by-step explanation:
5(a-1) -15 = 3(a+2) +4, distribute multiplication over subtraction and addition
5a -5 -15 = 3a +6 + 4, isolate the variable on one side
5a -3a = 6 +4 +5 +15, combine like terms
2a = 30, divide both sides by 2
a= 15
△ABCis reflected to form △A′B′C′. The vertices of △ABC are A(3, 1), B(1, 5), and C(6, 9). The vertices of △A′B′C′ are A′(−1, −3), B′(−5, −1), and C′(−9, −6). Which reflection results in the transformation of △ABC to △A′B′C′? Reflection across the x-axis reflection across the y-axis reflection across y = x reflection across y=−x I NEED HELP PLS The answer choies are: A. Reflection across the x-axis B. Reflection across the y-axis C. Reflection across y = x D. Reflection across y=−x
Answer: D) reflection across y = -x
Explanation:
When we reflect over y = x, we basically swap x and y. So for instance, the point (3,1) becomes (1,3).
When reflecting over y = -x, we will do the same thing but we'll make each coordinate swap in sign from positive to negative (or vice versa). The rule for reflecting over y = -x is [tex](x,y) \to (-y,-x)[/tex]
So if we apply that rule to point A(3,1) then it becomes A ' (-1, -3).
Similarly, B(1,5) moves to B ' (-5, -1)
Finally, C(6,9) becomes C ' (-9, -6)
What is the name for the marked angel ?
Answer:
A
Step-by-step explanation:
Answer:
The answer is <ead
please mark me brainliest
Let f(x) = 3x − 2 and g(x) = x + 1. Find (g ∘ f)(2).
Help plsssssssssssssssss
Answer:
(g ∘ f)(2) =5
Step-by-step explanation:
f(x) = 3x − 2
g(x) = x + 1
(g ∘ f)(2).
Find f(2) = 3(2) -2 = 6-2 = 4
Then find g(4) = 4+1 = 5
Divisibility rules with algebra
Answer:
D=8
Step-by-step explanation:
normal division rules
33 goes into 47 1 time
then it leaves 17D
if we divide 170 by 33, we get 5 and if we divide 179 by 33, we still get 5. So we have 17D-165. That leaves us with something that you multiply 33 with to have a 2 in the ones place so that you get a remainder of 2. (In order to get 2 in the remainder, we need a 2 in the ones place because 4-2=2. In order to get that we need to see which number multiplied with 33 would get us a number smaller than 179 but also has a 2 in the ones place. Theres only one number and thats 4. 33*4=132. So in order to get only 2 in the remainder, we need the rest to be subtracted. This means that 17D-165=134. This way we can see that D=8
Solve the inequality 12(1/2 x - 1/3) > 8 - 2x
O A. x>-1
O B. x > 3
O C. X>1/2
O D. x>3/2
Answer:
[tex]D. \\x>\frac{3}{2}[/tex]
Step-by-step explanation:
12(1/2x - 1/3) > 8 - 2x
6x - 4 > 8 - 2x
6x + 2x - 4 > 8 - 2x + 2x
8x - 4 > 8
8x - 4 + 4 > 8 + 4
8x > 12
8x ÷ 8 > 12 ÷ 8
x > 1.5
In a triangle ABC, angle BAC = 53° and angle ACB = 28°. If AB is produced to D, find angle CBD.
Angle CBD= 81°
I hope it helps you...
Answer:
81
Step-by-step explanation:
∠CBD is the exterior angle of the ΔABC.
Exterior angle property:
Exterior angle equals the sum of opposite interior angles.
∠CBD = ∠ABC + ∠ACB
= 53 + 28
= 81°
A cab company changes a 3$ flat rate addition to $1.50 per mile what is the y Intercept?
The y intercept would be the minimum amount charged, which would be the flat rate of $3
Answer: the y-intercept is 3
Can someone please just help me fill in those three boxes I’ve been struggling
evaluate and solve: y + 3 = –y + 9
The value of y is 3.
Answer:
Solution given;
: y + 3 = –y + 9
add +y on both term
y+y+3=-y+y+9
subtract both side by 3
2y+3-3=9-3
2y=6
divide both side by 2
2y/2=6/2
y=3
Answer:
y = 3
Step-by-step explanation:
y + 3 = –y + 9
Add y to each side
y+y + 3 = –y +y+ 9
2y +3 = 9
Subtract 3 from each side
2y+3-3 = 9-3
2y = 6
Divide by 2
2y/2 = 6/2
y = 3
PLEASE HELP ME! I REALLY NEED HELP
Answer:
a)
(i) 5.8 hours
(ii) 6.5 hours
(iii) 6 hours
(iv) 6 hours
b) 180 hours
Find the missing side or angle.
Round to the nearest tenth.
b=3
a=9
c=11
C= ?
Answer:
C=125°
Step-by-step explanation:
Hi there!
To find angle C, we can use the cosine law:
[tex]cosC=\frac{a^2+b^2-c^2}{2ab}[/tex]
Plug in the given information
[tex]cosC=\frac{9^2+3^2-11^2}{2(9)(3)}[/tex]
[tex]cosC=\frac{-31}{54}[/tex]
[tex]C=cos^-^1(\frac{-31}{54})[/tex]
[tex]C=cos^-^1(\frac{-31}{54})\\C=125[/tex]
Therefore, angle C is approximately 125 degrees.
I hope this helps!
If m ≠ 1 and mn - 3 = 3 - n , then what is the value of n?
A) 6/ m+1
B) 6/ m-1
C) 6/ m+n
D) 6/ m-n
[tex]n = \frac{6}{m + 1} [/tex]
Hope it helps you...
The value of n is n= 6/( m+1).
What is expression?An expression is a set of terms combined using the operations +, – , x or , /.
Given:
mn - 3 = 3 - n
mn + n = 6
n(m+ 1) =6
n= 6/( m+1)
Learn more about expression here:
https://brainly.com/question/14083225
#SPJ2
Find the missing side lengths
Answer:
x = 11√3
y = 11
Step-by-step explanation:
Let 60 be the reference angle
sin 60 = p/h
√3/2 = x/22
or, 22√3 = 2x
or, x = (22√3)/2
so, x = 11√3
now
[tex]h^2 = p^2 + b^2\\or, 22^2 = (11\sqrt{3} )^2+y^2\\or, 484 = 363 + y^2\\or, 484-363 = y^2\\or, 121 = y^2\\or, \sqrt{121} = y\\so, y = 11[/tex]
plsssss helpp in the next 2 min gives 10 points
Answer:
The answer is 144,5
Step-by-step explanation:
144,5/170×100 =85%
A basketball team received a care package and split it evenly among
5 players. If each player received 9 candy bars, how many candy bars
were in the care package?
Help please
Answer:
45
Step-by-step explanation:
9x5
Express 0.00506 in standard form
Answer:
[tex]5.06 x 10^{-3}[/tex]
Step-by-step explanation:
Move decimal 3 place to right.
Because the decimal was moved to right, the exponent is negative.
How do I simplify this? With steps please :)
Answer:
[tex]{ \tt{ = \frac{ {p}^{2} + 8p + 16 }{ {p}^{2} - 16 } }} \\ \\ = { \tt{ \frac{ {(x + 4)}^{2} }{(x - 4)(x + 4)} }} \\ \\ = { \tt{ \frac{(x + 4)}{(x - 4)} }}[/tex]
If the discriminant of an equation is zero, which of the following is true of the equation?
[tex]\sf Your \: question \: is \: incomplete. \: [/tex]
______________________
[tex]\sf \: I \: believe \: this \: is \: the \: answer \: you \: wanted[/tex] ⟹
[tex]\sf If \: the \: discriminant \: of \: an \: equation \: is \: zero, \: then \\ \sf \: the \: equation \: will \: have \:\underline{ 1 \: real \: solution \: with \: real \: and \: equal \: roots}.[/tex]
[tex]\boxed{ \sf{Explanation}} [/tex]
[tex]\sf If \: discriminant \: of \: quadratic \: equation \: ax^{2} + bx + c \: \\ \sf is \: b^{2} - 4ac = 0 \: then \: it \: will \: have \\ \sf↦\underline{1 \: real \: solution \: with \: real \: and \: equal \: roots.} [/tex]
Answer:
see explanation
Step-by-step explanation:
If b² - 4ac = 0
Then the roots are real and equal
pls help its timed no fake answers i cant afford to fail
Answer:
It's B, I tried using mathaway and that's the closest to the answer I got. Try it. I always use mathaway for any math problems, use that for now on if you're stuck
Step-by-step explanation:
If there were 36 candies and only 12 children, how many candies would each child get?
Answer:
3 each
Step-by-step explanation:
36 / 12 = 3
.................................................
Can someone explain and give an example of spurious correlation?
Answer:
A spurious correlation wrongly implies a cause and effect between two variables. For example, the number of astronauts dying in spacecraft is directly correlated to seatbelt use in cars: Use your seatbelt and save an astronaut life!
Interesting correlations are easy to find, but many will turn out to be spurious. Three examples are the skirt length theory, the Super Bowl indicator, and a suggested correlation between race and college completion rates.
Step-by-step explanation:
please answer the question below! first to answer correctly, I will mark as brainliest.
The probability of not winning would be :
1 - probability of winning
This is written as:
1 - n/n+3
Now to simplify as a single fraction rewrite as:
N+3/n+3 - n/n+3
Simplify to get : 3/n+3
order the set of irrational numbers from least to greatest
Answer:
answer is A
hope it helps please mark as brainliest answer and give me thanks
#Dhruv hereFind square root of 0.0324
Answer:
0.18
Step-by-step explanation: